Deeplex Sequencing of Mycobacterium Tuberculosis Strains Isolated in Kosovo - Rrezarta Bajrami; Alina Minias; Greta Lila (Journal of Global Antimicrobial Resistance)
INTRODUCTION: According to the World Health Organization, there were 10 million new tuberculosis cases, and the disease caused 1.5 million deaths in 2022. The incidence of tuberculosis in Kosovo was 34.4 per 100,000 population in 2022. To date, there is no information regarding the genetic composition of the population of the causative agent Mycobacterium tuberculosis, circulating in Kosovo. MATERIALS-METHODS: We investigated the genetics of M. tuberculosis in Kosovo through targeted sequencing. Twenty positive sputum samples were collected in 2023 in hospitals in Kosovo, following identification through Ziehl- Nielsen staining, primary culture was performed using solid BBL Lowenstein-Jensen LJ and liquid BBL Mycobacteria Growth Indicator Tube and Gene Xpert confirmation. We used commercial test Deeplex TB Myc on the MiSeq Illumina platform to identify mutations in 18 drug resistance-associated genes and to determine the spoligotype pattern. RESULTS: All of the samples were successfully genotyped. All analyzed strains belonged to Lineage 4. Two strains shared an identical spoligotype pattern. Thirteen strains were sensitive to all anti-tuberculosis, while two strains were MDR/RR-TB, two were fluoroquinolone-resistant, and one was pre-extensively drug-resistant (MDR/RR-TB and fluoroquinolone-resistant). CONCLUSIONS: We found that all analyzed M. tuberculosis strains belong to the most prevalent in Europe lineage 4, and five out of 18 of them were drug-resistant. Two drug-sensitive strains shared identical spoligotypes, suggesting a transmission event not identified in the epidemiological investigation. Our results support introducing next-generation sequencing (NGS) in routine tuberculosis diagnostics in Kosovo to identify drug resistance and provide genotyping information for epidemiological surveillance.